Cell adhesion molecules involved in the leukocyte recruitment induced by venom of the snake Bothrops jararaca - Stella R. Zamuner; Catarina F. P. Teixeira (Hindawi Limited, 2002)
It has been shown that Bothrops jararaca venom (BjV) induces a significant leukocyte accumulation, mainly neutrophils, at the local of tissue damage. Therefore, the role of the adhesion molecules intercellular adhesion molecule-1 (ICAM-1), LECAM-1, CD18, leukocyte function-associated antigen-1 (LFA-1) and platelet endothelial cell adhesion molecule-1 (PECAM-1) on the BjV-induced neutrophil accumulation and the correlation with release of LTB4, TXA2, tumor necrosis factor-α, interleukin (IL)-1 and IL-6 have been investigated. Anti-mouse LECAM-1, LFA-1, ICAM-1 and PECAM-1 monoclonal antibody injection resulted in a reduction of 42%, 80%, 66% and 67%, respectively, of neutrophil accumulation induced by BjV (250 μg/kg, intraperitoneal) injection in male mice compared with isotype-matched control injected animals. The anti-mouse CD18 monoclonal antibody had no significant effect on venom-induced neutrophil accumulation. Concentrations of LTB4, TXA2, IL-6 and TNF-α were significant increased in the peritoneal exudates of animals injected with venom, whereas no increment in IL-1 was detected. This results suggest that ICAM-1, LECAM-1, LFA-1 and PECAM-1, but not CD18, adhesion molecules are involved in the recruitment of neutrophils into the inflammatory site induced by BjV. This is the first in vivo evidence that snake venom is able to up-regulate the expression of adhesion molecules by both leukocytes and endothelial cells. This venom effect may be indirect, probably through the release of the inflammatory mediators evidenced in the present study.